2016
DOI: 10.21037/jtd.2016.08.82
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of immunohistochemical markers in malignant thymic epithelial tumors

Abstract: Background: Thymic epithelial tumors (TET) are rare neoplasms with inconsistent treatment strategies.When researching for molecular pathways to find new therapies, the correlation between specific molecular markers and outcome has only rarely been investigated. The aim of this study was to investigate the correlation between survival, metastatic potential and invasiveness of aggressive subtypes of TET and immunohistochemical markers. Methods: Overall survival (OS), disease-free survival (DFS), progression-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…p21 is phosphorylated by Akt1 and murine leukemia virus (Pim-1) at threonoine-145 in order to keep it in the cytoplasm [1, 71] and cancers with high p21 cytoplasmic/nuclear ratio are thought to be more aggressive. Therefore, our finding that AI-resistant MCF-7:5C cells have very high expression of IFITM1 but very low nuclear p21 expression is consistent with their highly aggressive phenotype both in vitro and in vivo [20, 40, 75]. …”
Section: Discussionmentioning
confidence: 66%
“…p21 is phosphorylated by Akt1 and murine leukemia virus (Pim-1) at threonoine-145 in order to keep it in the cytoplasm [1, 71] and cancers with high p21 cytoplasmic/nuclear ratio are thought to be more aggressive. Therefore, our finding that AI-resistant MCF-7:5C cells have very high expression of IFITM1 but very low nuclear p21 expression is consistent with their highly aggressive phenotype both in vitro and in vivo [20, 40, 75]. …”
Section: Discussionmentioning
confidence: 66%
“…These tumors represent a distinct histologic subtype of thymic carcinoma which is characterized by highly atypical tumor cells that grow in cords, nests, and trabeculae and often contain a dense lymphoplasmacytic infiltrate in the stroma [4]. Recently, several studies have identified increased expression of PD-L1 and PD-1 in thymic epithelial neoplasms including thymomas and thymic carcinomas suggesting that these lesions may be responsive to PD-L1/PD-1 inhibitor therapy [5][6][7][8][9][10][11][12][13][14]. However, the expression of PDL-1 in lymphoepithelioma-like carcinoma of the thymus has not yet been specifically addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Fine-needle aspiration cytology and core needle biopsies are the gold standard in the primary diagnosis of patients with breast neoplasms to observe changes in morphology. Immunohistochemical markers can confirm changes observed by hematoxylin & eosin staining [16]. On balance, the disease should be detected, diagnosed, and treated early.…”
Section: Discussionmentioning
confidence: 98%